The Correlation Between Electrical Resistivity Tomography and Borehole Data at a Coastal Semi-Developed Area - Muhammad Nizam Zakaria,; Obiya, Hiroyuki; Ahmad Tajudin, Saiful Azhar bin; Zahari, Muhammad Nur Hidayat bin; Madun, Aziman bin; Jasme, Amir; Ishak, Mohd Fakhrurrazi (International Journal of Integrated Engineering, 2026)
This study explores the correlation between Electrical Resistivity Tomography (ERT) and borehole (borelog) data to characterize subsurface properties at a coastal semi-developed area in Melaka, Malaysia. The objective is to assess how resistivity values correspond to soil or rock information obtained from boreholes, with a focus on geological features, material types, and groundwater levels. A strong linear correlation (R² = 0.93) was established between resistivity values and SPT N-values, especially where ERT lines were closely aligned with borehole locations. The research evaluates the reliability and applicability of ERT as a non-destructive method, comparing it to traditional point-based techniques like the Standard Penetration Test (SPT). By integrating continuous ERT profiles with borehole data, the study addresses trade-offs in resolution and accuracy between these methods. Results show a strong correlation between resistivity and SPT N-values, particularly in areas where ERT lines were closely aligned with boreholes. The findings highlight the applicability of ERT as a complementary tool for preliminary geotechnical investigation and slope or coastal site assessment in urban and geologically complex environments.